Crystal-field effects in Er 3 + - and Yb 3 + -doped hexagonal NaYF 4 nanoparticles - García Flores, A. F. (2017)
Since the up-conversion phenomenon in rare-earths (REs) doped NaYF4 is strongly affected by the crystal electric field (CF), determining the CF parameters, wave functions, and scheme of the energy levels of the RE J multiplets could be crucial to improve and tune the up-conversion efficiency. In this work, the temperature and magnetic field dependent magnetization of NaY1−x[Er(Yb)]xF4 hexagonal nanoparticles (NPs) is reported. The data were best fit using the appropriated CF Hamiltonian for the J=15/2(J=7/2) ground state multiplet of Er3+(Yb3+) ions. The B02, B04, B06, and B66 CF parameters were considered in the Hamiltonian for RE ions located at the hexagonal C3h point symmetry site of the NaYF4 host lattice. These results allowed us to predict an overall CF splitting of ∼214 (∼356 ) for Er3+(Yb3+) and the wave functions and their energy levels for the J=15/2 (J=7/2) ground state multiplet which are in good agreement with the low temperature electron spin resonance experiments. Besides, our measurements allowed us to calculate all the excited CF J multiplets that yield to a good estimation of the up-conversion light emission linewidth. The nonlinear optical light emission of the studied NaY1−x[Er(Yb)]xF4 hexagonal NPs was also compared with the most efficient up-conversion codoped NaY1−x−yErxY by F4 hexagonal NPs.